Information on operational sea ice products and current and future activities of the German ice service - Aldenhoff, Wiebke; Holfort, Jürgen (Frontiers in Marine Science, 2024)
The ice service at the German Federal Maritime and Hydrographic Agency and its predecessors has been committed to the safety and easiness of ship navigation for more than 100 years. Within this paper, an overview of the operational products issued by the German ice service on a daily to weekly basis throughout the northern hemisphere winter season is given. These comprise written reports, ice charts, NAVTEX messages, and messages via the Global Telecommunication System to inform about the sea ice situation in German coastal waters, the Baltic Sea, and worldwide. Furthermore, the ice service has systematically collected ice observation data along the German North Sea and Baltic Sea coast since the winter of 1896/1897. The history of the German ice service is presented to put the sea ice data into context of the observation technologies used in the course of the existence of the ice service. These long-term observations enable climatological analyses of the sea ice cover in German coastal waters necessary for the safe operation of offshore infrastructure. An evaluation of the data shows a recent decline in sea ice occurrence in the Baltic Sea and German Bight. Current work is ongoing to preserve more of the historic data in digital form and also to transform the products to conform to modern standards in digital technologies and interactive solutions for the customers.